Inhaled corticosteroid dose is associated with Pseudomonas aeruginosa infection in severe COPD - Antonio Oliver; Borja G Cosío; Hanaa Shafiek; Javier Verdú; Amanda Iglesias; Lluisa Ramon-Clar; Nuria Toledo-Pons; Carla Lopez-Causape; Carlos Juan; Pablo Fraile-Ribot (BMJ Open Respiratory Research)
Introduction Patients with chronic obstructive pulmonary disease (COPD) with frequent exacerbations (ExCOPD) are commonly treated with inhaled corticosteroids (ICS) and are at risk of infections caused by potential pathogenic bacteria (PPB) including Pseudomonas aeruginosa (PsA).Objectives To investigate the association between the use of ICS and PsA infection among ExCOPD.Methods Case–control study with longitudinal follow-up that recruited ExCOPD after a hospitalisation due to exacerbation between 2012 and 2020. Patients with isolation of PsA (COPD-PsA) in sputum either during admission or follow-up were compared with those with other or no PPB. Clinical, functional characteristics, DDD, use of ICS and survival were evaluated. Cox regression analysis was performed to evaluate the risk factors associated to PsA infection and mortality.Results 358 patients (78% male, mean age 73±9 years) were enrolled and followed up for a median of 4 years (IQR=3–8). 173 patients (48.3%) had at least a positive culture for PsA. COPD-PsA had more frequent exacerbations, more severe airflow limitation and higher mortality (69.4% vs 46.5%, p<0.001). There were no differences in the use of ICS between groups but the dose of ICS was significantly higher among COPD-PsA (median of 500 µg fluticasone propionate equivalents (IQR=250–1000) vs 400 µg (IQR=200–1000), p=0.007). Blood eosinophil count (BEC) was not different between ICS users and non-users. In multivariate analysis, the dose of ICS was an independent risk factor for PsA infection and mortality but not ICS use.Conclusions ICS dose, but not its use, could be a risk factor for PsA infection in patients with severe COPD regardless of BEC.